Studies on mechanical behavior and microstructural analysis of tailor welded blanks of Ti–6Al–4V titanium alloy sheet. Issue 14 (21st April 2016) - Karpagaraj, A.; Siva Shanmugam, N.; Sankaranarayanasamy, K.
Abstract: Abstract : In the present study, Ti–6Al–4V alloy sheets having a thickness of 1.6 mm and 2 mm are chosen for carrying out weldability studies using gas tungsten arc welding (GTAW) process. The quality of the weld was examined through metallographic (macro- and micrographs) analyses. The welded specimens were subjected to mechanical tests to examine the behavior of tailor welded blanks (TWBs). Grain coarsening at fusion zone (FZ) and heat affected zone was confirmed through optical microscope. Transmission electron microscopy images showed the presence of thin α-phases surrounded by β-grains at FZ. The maximum hardness distribution of 383 HV is obtained at FZ. Tensile test results revealed an increase of 3.58% strength as compared to the thin base metal. At fracture surface, the presence of various sized dimples was identified through SEM. Erichsen cupping test showed that formability performance of the TWB was affected by a negligible percentage.